Study Some Parameters That Effecting On The Coating Efficiency Of Turbine Blades Produced By Thermal Spraying - Jassim, l.K; Farman, A.Kh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Flame thermal spray technique has been used to produce a cermets  composite coating  based on  powders of ceramic oxides  (AhOJ) reinforced by mineral powders as bonding material ( Ni - AI ) at different rates on Inconel substrates , after preparing it by grit blasting.After completing the best parameters of coating such as distance of spraying , surface roughness and angle of spraying , the tests of porosity ,  hardness , microstructure and thermal cycling  have been made.The experimental results show that all properties of coating were effected after heat treatment. The best value of  heat treatmen t is at (I 000Â°C)  for  (l.Shr)  in  which  the  results  show  a  good  interface between layers with vel)' small pores.Also we studied the effect of thermal cycl ing at high temperature for several times to see the effect of heati ng on the top surface of layer coating.